Putting Factions ‘Back in’ the Civil-Military Relations EquationGenesis, Maturation and Distortion of the Bangladeshi Army - Jérémie Codron (South Asia Multidisciplinary Academic Journal, 2007)
This paper attempts to highlight two characteristics of the Bangladeshi army, namely factionalism and politicization. It shows how they hampered the institutionalization of civil-military relations in this country, and also suggests that the political power’s manoeuvres aggravated the army’s structural instability born of the Independence war. While arguing that the military’s professionalism and the institutionalization of the armed forces’ role were, in fact, encouraged during the 1980s military rule, the main thesis points to the return of civilians to power in 1991, which reintroduced partisan cleavages into the army and threatened the stability of civil-military relations. The trajectory of the Bangladeshi army indeed suggests that democratization does not necessarily lead to a higher degree of professionalism in armed forces.